The Development of Integrated Thematic Learning Devices Based on Interactive Compensatory Model to Improve Students’ Reading Comprehension in Islamic Elementary School - Ryan Dwi Puspita; Susanti Agustina; Asep Deni Gustiana; Duhita Savira Wardani (Jurnal Pendidikan Islam, 2020)
This study aims to examine the effect of using interactive compensatory model (ICM)-based integrated thematic learning tools to improve students’ reading comprehension of information text comprehension for fifth grade elementary school. This research was conducted in three stages. The first phase of the preliminary study included a literature study, field surveys and expert-validated initial product preparation. The second stage of development included limited trials and extensive trials through experimental methods. The third stage was product testing and socialization of the results to try out its efficacy. Data were obtained through observation, interviews, questionnaires and test (pre-test and post-test). This study used a sample of 504 grade fifth students in 12 elementary schools in Bandung Regency. The results of this study indicate that the use of ICM-based integrated thematic learning tools has a significant effect on students’ improvement for reading comprehension on information text for fifth grade elementary school. This is evidenced by the difference in students’ reading comprehension ability before and after learning using ICM-based integrated thematic learning tools. This research has implications for the ease with which teachers can achieve learning objectives with the support of teaching materials, media, worksheets and interesting and practical activities that can stimulate students to improve their reading comprehension skills.